Some reflections on the 10th anniversary of Tecnoscienza - Lucy Suchman (Tecnoscienza, 2020)
How can STS move towards a greater pluriversality? How can we question the taken for granted of STS scholarship and geopolitics, so as to engage across radically different worlds? Thinking through a decade of Tecnoscienza and bridging the articles published in the 2010 and the 2019 volumes, the contribution reflects upon possible lines of future STS inquiry.